Allele frequencies of acaricide resistance-associated specific nucleotide polymorphisms in Rhipicephalus microplus and Rhipicephalus decoloratus in Manicaland Zimbabwe - Crafford, Jan Ernst (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.